THE USE Of BLENDED LEARNING MODEL TO ENHANCE STUDENT'S LEARNING INTEREST IN ENGLISH - Lanlan Muhria (English Language Education Department, Universitas Majalengka, 2022)
The goal of this study is to ascertain whether employing a blended learning paradigm has increased students' interest in learning. In this study, a descriptive method is combined with a qualitative approach. The population of this study consisted of 36 students in class II-A of the STKIP Yasika Mathematics Education Study Program, which used purposive sampling as its sample technique. Data reduction, data presentation, and conclusion drawing or verification are used in the analysis of data gathering procedures, which include surveys, interviews, and observations. The results showed that, on average, 86 percent of students in class II-A of the Mathematics Education Study Program in STKIP Yasika exhibited a greater interest in studying English when blended learning is used. These results include the following indicators: 1) feelings of enjoyment with the very strong category (89%); 2) attention with the very strong category (83%); 3) very high interest in learning (91%); and 3) actively involved with the very strong category (81%)